PENGARUH COACHING, SPIRITUALITAS DAN KECERDASAN SOSIAL TERHADAP KEPEMIMPINAN - Pramudianto Pramudianto (LP2M Universitas Bina Bangsa, 2021)
The purpose of this research is to know comprehensively the influence of coaching and social intelligence application toward transformational leadership and servant leadership to the principal of kindergarten at BPK PENABUR Jakarta. Respondents who filled this questionnaire amounted to 156 kindergarten teachers in BPK PENABUR Jakarta. Hypothesis in this research is tested by using data analysis technique with SEM-PLS software especially Warpls version 6 software. The results of this study conclude that (1) coaching affects transformational leadership; (2) coaching affects servant leadership; (3) social intelligence affects transformational leadership; and (4) social intelligence affects servant leadership. Thus, the highest influence is coaching on transformational leadership. Therefore, to improve the leadership skills of the principal of kindergarten in BPK PENABUR Jakarta, it is necessary to apply coaching and transformational leadership type. The purpose of the implementation is expected to improve individual performance so as to achieve the goals in accordance with the vision and mission of the institution.